(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The wild yam Dioscorea praehensilis is widely consumed as famine food in Côte d’Ivoire and numbers of African countries mainly after boiling. Raw and boiled wild yam tubers (Dioscorea praehensilis) flours were analyzed for proximate contents such as ash, crude protein, carbohydrate, Moisture energy s using standard procedures and methods. (YT0) was used as control compared to tubers boiled for 5 minutes (YT5), 10 minutes (YT10), 20 minutes (YT20), 30 minutes (YT30) and 40 minutes (YT40). The crude protein contents (9.13 g/100g DM), ash (1.02 g/100g DM), lipid (3.25 g/100g DM), carbohydrate (89.21 g/100g DM) and Moisture (13.04%) were significantly (p<0.05) lowered in the boiled tubers. Even boiled, Dioscorea praehensilis remained a good energy supply product with about 391 kCal/100g. The evolution of parameters essentially the decrease of moisture content showed that for the storage and nutritional purpose, boiling had both positive and negative effect on yam tuber flours. A cooking time of between 5 and 40 min at 100°C was recommended for D. praehensilis.